Pectin Extraction of Citrus aurantifolia’s Peel Using Microwave Assisted Extraction - Megawati Megawati; Ruth Samaria Pardede; Desy Putri Nawangsari (Seminar Nasional Teknik Kimia Kejuangan, 2017)
This research investigated pectin extraction of lime (Citrus aurantifolia) peel with oxalic acid solvent using Microwave Assisted Extraction (MAE) method. Prior of usage, lime peel was dried and ground to reduce water content and increase contact surface. Extraction using conventional method was also performed to study comparison with extraction using MAE. Extraction using MAE was performed to 10 g material and 300 mL oxalic acid 0.2 N. Pectin solution was then dehydrated using 96% ethanol (1:1 v/v) to get pure pectin. Experiment showed that MAE method obtained pectin with shorter duration (6 minutes with rendement 10.9%) compared to conventional method (20 minutes with rendement 11.8%). Pectin extraction using MAE for 6 minutes at 450 Watt produced 10.9 g pectin, higher than 350 W which produced 10.2 g. At 450 Watt with duration of 2, 3, 4, 5 and 6 minutes, pectin obtained are 0.75; 0.87; 0.93; 1.01 and 1.09 g respectively. The result of FTIR (Fourier Transform Infrared Spectroscopy) and other properties analysis showed that pectin consists of ester, cyclic-carbon, carboxylic and carbonile; and also 8.15% metoxil, 74.57% galacturonic acid, 2.7% water, 0.236% ash, esterification degree of 79.2%, and equivalent weight of 612.